2014
DOI: 10.1111/1469-0691.12702
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus ‘Down Under’: contemporary epidemiology of S. aureus in Australia, New Zealand, and the South West Pacific

Abstract: The clinical and molecular epidemiology of Staphylococcus aureus disease has changed considerably over the past two decades, particularly with the emergence and spread of community-associated methicillin-resistant S. aureus (CA-MRSA) clones. Indeed, some of the first global descriptions of CA-MRSA were from remote indigenous communities in Western Australia, and from Pacific Peoples in New Zealand. The epidemiology of S. aureus infections in the South West Pacific has several unique features, largely because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 62 publications
4
33
0
Order By: Relevance
“…The association of CC121 with SSTI is consistent with the international literature and CC121 is phenotypically usually MSSA [22]. The molecular epidemiology of MSSA infections has been studied in less detail than CA-MRSA [23], but CC121 is commonly associated with SSTIs in Australia. However, the high prevalence of CC121 in our study (30%) is greater than that reported elsewhere in the Northern Territory ‘Top End’ and metropolitan centers [9, 18], and may be a unique feature of the Central Australian region.…”
Section: Discussionsupporting
confidence: 77%
“…The association of CC121 with SSTI is consistent with the international literature and CC121 is phenotypically usually MSSA [22]. The molecular epidemiology of MSSA infections has been studied in less detail than CA-MRSA [23], but CC121 is commonly associated with SSTIs in Australia. However, the high prevalence of CC121 in our study (30%) is greater than that reported elsewhere in the Northern Territory ‘Top End’ and metropolitan centers [9, 18], and may be a unique feature of the Central Australian region.…”
Section: Discussionsupporting
confidence: 77%
“…Community‐acquired methicillin‐resistant Staphylococcus aureus (‘CA‐MRSA’) now accounts for 25% of S. aureus infections in some parts of Australia, with risk factors including race (Aboriginal, Maori, Pacific Islander), communal living (prisons, boarding houses), i.v. drug use and poor self‐care . Dominant CA‐MRSA clones and resistance patterns can vary widely between locations, so local data and early infectious diseases specialist input are required to guide empiric therapy …”
Section: Antimicrobialsmentioning
confidence: 99%
“…drug use and poor self-care. 12,13 Dominant CA-MRSA clones and resistance patterns can vary widely between locations, so local data and early infectious diseases specialist input are required to guide empiric therapy. 14…”
Section: Antimicrobial Selectionmentioning
confidence: 99%
“…methicillin) (Van Hal et al, 2007). The prevalence of MRSA infections have increased dramatically over the past two decades (Williamson et al, 2014). According to Baiu & AL-Abdli (2015), due to antibiotics resistance, MRSA infections required more complicated treatment.…”
Section: Methicillin Resistant S Aureus (Mrsa) and Coagulase Negativementioning
confidence: 99%